Er:YAG Laser Debonding of Lithium Disilicate Laminate Veneers: Effect of Laser Power Settings and Veneer Thickness on The Debonding Time and Pulpal Temperature: Er:YAG Laser Debonding of Laminate Veneers - El-Damanhoury, Hatem M.; Salman, Basheer; Kheder, Waad; Benzina, Dalenda (Journal of Lasers in Medical Sciences, 2022)
Aim: This study aimed to investigate the influence of different laser power output on the pulpal temperature and the time required to achieve debonding of lithium disilicate laminate veneers with two different thicknesses. Methods: labial enamel of forty-eight maxillary central incisors was flattened and polished. The teeth restored with flat lithium disilicate ceramic veneers (4.0 mm X 6.0 mm), with one of two different thicknesses (0.5 and 1.0 mm). Veneer debonding was done using Er:YAG laser (Fidelis AT, Fotona) with 2940 nm wavelength and a 100 μm pulse duration (VSP mode) and 10 Hz and one of three laser power output settings: 1.5W (150 mj), 3W (300 mj), and 5.4W (360 mj) (n=8). The veneer debonding time and intra-pulpal temperature changes (∆T) were measured. Statistical analysis was done using Two-way ANOVA and Bonferroni post-hoc test (a = 0.05). Correlation between the debonding time and temperature changes was computed using a Pearson’s correlation. Results: Debonding 1.0 mm veneers with 1W power recorded the longest time (p<0.05), while debonding 0.5 veneers with 3W and 5.4 W recorded the shortest times (p<0.05). There was a significant decrease in ∆T with the increase of laser power. A low correlation was found between the debonding time and ∆T (R² = 0.113) Conclusions: The laser power and veneer thickness are crucial factors in debonding, with the thinner veneers being faster to remove. When debonding thick veneers, a laser power output 5.4W is more efficient and less harmful to the pulp tissues.